Participation Costs and the Sensitivity of Fund Flows to Past Performance - HUANG, JENNIFER; WEI, KELSEY D.; YAN, HONG (Journal of Finance, 2007)
ABSTRACT We present a simple rational model to highlight the effect of investors' participation costs on the response of mutual fund flows to past fund performance. By incorporating participation costs into a model in which investors learn about managers' ability from past returns, we show that mutual funds with lower participation costs have a higher flow sensitivity to medium performance and a lower flow sensitivity to high performance than their higher‐cost peers. Using various fund characteristics as proxies for the reduction in participation costs, we provide empirical evidence supporting the model's implications for the asymmetric flow‐performance relationship.